Mechanisms of PEDF-mediated protection against reactive oxygen species damage in diabetic retinopathy and neuropathy - Elahy, M.; Baindur-Hudson, S.; Newsholme, Philip; Dass, Crispin (BioScientifica, 2014)
Pigment epithelium-derived factor (PEDF) is a pluripotent glycoprotein belonging to the serpin family. PEDF can stimulate several physiological processes such as angiogenesis, cell proliferation and survival. Oxidative stress plays an important role in the occurrence of diabetic retinopathy (DR) which is the major cause of blindness in young diabetic adults. PEDF plays a protective role in DR and there is accumulating evidence of the neuroprotective effect of PEDF. In this paper, we review the role of PEDF and the mechanisms involved in its antioxidative, anti-inflammatory and neuroprotective properties.